2010
DOI: 10.1186/1742-9994-7-16
|View full text |Cite
|
Sign up to set email alerts
|

The integrative future of taxonomy

Abstract: BackgroundTaxonomy is the biological discipline that identifies, describes, classifies and names extant and extinct species and other taxa. Nowadays, species taxonomy is confronted with the challenge to fully incorporate new theory, methods and data from disciplines that study the origin, limits and evolution of species.ResultsIntegrative taxonomy has been proposed as a framework to bring together these conceptual and methodological developments. Here we review perspectives for an integrative taxonomy that dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
1,179
1
36

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,521 publications
(1,241 citation statements)
references
References 101 publications
25
1,179
1
36
Order By: Relevance
“…molecular, morphological, ecological, and behavioral) for taxonomy is expected to reduce subjectivity in delimiting taxa (Dayrat, 2005;Leaché et al, 2009;Padial et al, 2010;Schlick-Steiner et al, 2010;Yeates et al, 2011). However, in situations where cryptic species with indistinct morphological and ecological properties are present, integrative methods will not yield a clear result since different types of data may yield discordant conclusions (Fujita et al, 2012;Wiens and Penkrot, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…molecular, morphological, ecological, and behavioral) for taxonomy is expected to reduce subjectivity in delimiting taxa (Dayrat, 2005;Leaché et al, 2009;Padial et al, 2010;Schlick-Steiner et al, 2010;Yeates et al, 2011). However, in situations where cryptic species with indistinct morphological and ecological properties are present, integrative methods will not yield a clear result since different types of data may yield discordant conclusions (Fujita et al, 2012;Wiens and Penkrot, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These are necessarily subjective judgments. Lymbery et al (2015) suggested that an integrative or iterative approach (see Padial et al, 2010;Yeates et al, 2011), using molecular, ecological and morphological data together, might provide more objectivity, but unfortunately we know very little about the heritability of morphological and ecological traits in Echinococcus spp. The best 22 way to resolve this issue may be to use multilocus genotypic data in a coalescent-based approach to species delimitation (see section 7).…”
mentioning
confidence: 99%
“…If the group was monophyletic we then looked for groups with 300 high clade support, i.e., parsimony and likelihood bootstrap sup-301 port P75% and Bayesian posterior probability P0.95, as uncon-302 firmed candidate species (Padial et al, 2010). We then checked 303 for minimal genetic divergences of 1.0% at 12S and 5% divergence 304 at Cytb.…”
mentioning
confidence: 99%
“…We then checked 303 for minimal genetic divergences of 1.0% at 12S and 5% divergence 304 at Cytb. Although the specific levels of statistical support and levels 305 of genetic divergence are arbitrary, our goal was simply to flag 306 well-supported monophyletic clades with a notable genetic diver-307 gence as candidate species (Padial et al, 2010 (Carstens et al, 2013;Miralles and Vences, 2013 (Carstens et al,374 2013; Miralles and Vences, 2013 (Ree and Smith, 2008 we used four regions of high amphibian endemism (Duellman, Cytb data were available for 91% and 96% of samples, respectively. Table 2).…”
mentioning
confidence: 99%